Preview of a detailed techno-economic analysis of diesel from algae: economic feasibility under sustainability constraints requires sustained unrealistically high algae yields if public subsidies are absent. - Amanor-Boadu, Vincent; Pfromm, Peter H.; Nelson, Richard (My University, 2012)
A detailed economical analysis of producing algae-derived biodiesel via open-pond aquaculture has been performed and is in peer-review for publication. The results of the economical analysis confirm the critical limitation of economic feasibility by achievable and fundamentally plausible biomass yields.
Keywords: Algae; Diesel; Open-pond aquaculture; Economic feasibility; Carbon dioxide; Yield